Balancing the dual nature of glycotoxins: interplay of diet, digestion, and gut microbiome - Semchyshyn, Halyna (Frontiers in Nutrition, 2025)
Glycation chemistry, both in vitro and in vivo, is well-studied and known to result in a variety of products—from early glycation products, reactive carbonyl and oxygen species (RCS and ROS, respectively) to advanced glycation end products (AGEs). Exogenous glycation products from the regular diet contribute substantially to the total AGE burden, often exceeding endogenous formation. AGEs and other products of glycation, whether formed endogenously or derived exogenously, may have similar biological effects and are mainly known for their harmful impact, therefore, the term “glycotoxins” is used to emphasize the toxicity of certain of them. Nevertheless, the human body as well as gut microbiome have adapted to the presence of glycation products and can even use them beneficially at low concentrations. Maintaining an appropriate balance of glycotoxins depends largely on digestion in the gastrointestinal tract, mediated by both host and microbiome enzymes. The fate of dietary glycation products in the gut strongly depends on their interaction with the intestinal microbiota. A key open question is how human and microbial enzymes work together to degrade AGEs and maintain their concentrations within a potentially “beneficial” range. This review is focused on the metabolism and digestion of glycation products by both human and microbial enzymes, highlighting their dual nature and overall impact on human health.